The Influence of Independence, Professionalism, and Auditor Performance on Audit Quality: A Case Study of Public Accounting Firms in Jakarta - Naibaho, Yanti Desipa; Sari, Fangela Myas; Nainggolan, Olivia Venessa Boru (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to examine and analyze the influence of auditor independence, auditor professionalism, and auditor performance on audit quality. The primary focus of this study is to determine which variables have a significant impact on audit quality within the context of Public Accounting Firms in Jakarta. This research employs a quantitative, correlational approach. Primary data were collected through a survey method using a closed questionnaire, which was distributed directly to 30 auditors working in three Public-Private Agreements (PKAs) in Jakarta. The sampling technique used was probability sampling, with a census sampling approach. Data analysis was conducted using the Partial Least Squares - Structural Equation Modeling (PLS-SEM) approach through WarpPLS software version 8.0. The results of the study indicate that the auditor professionalism variable has a positive and significant effect on audit quality. Conversely, the auditor independence and auditor performance variables do not show a significant impact on audit quality. These findings suggest that improvements in audit quality are more closely tied to the professional attitudes of auditors than to other variables. This study highlights the importance of cultivating professional values in audit practice as a crucial step in achieving optimal audit quality. The results of this study can serve as a reference for the development of auditor training policies and performance evaluation in public accounting firms.